The Use of Swadling and Skin Wrap in Regulation of Body Temperature of Premature Babies - Padila, Padila; Andri, Juli; Andrianto, Muhammad Bagus; J, Harsismanto; Sartika, Andry (JOSING: Journal of Nursing and Health, 2024)
This study aims to determine the effectiveness of using swaddling and skin wrap in regulating the body temperature of premature babies in the NICU room of RSHD Kota Bengkulu. The research method used is quasi-experimental with the design of this study using two group pretest posttest. The results showed that the average body temperature of premature babies in the NICU room of RSHD Kota Bengkulu before using swaddling was 35.890C. After using swaddling the average body temperature of premature babies increased to 37.04oC. The average body temperature of premature babies before using skin wrap was 35.930C and after using skin wrap the average body temperature of premature babies increased to 37.180C. The results of the analysis using paired sample t-test obtained a p-value of 0.000 <0.05. In conclusion, the use of swaddling and skin wrap is effective in regulating the body temperature of premature babies in the NICU room of RSHD Kota Bengkulu. Keywords: Premature Babies, Swaddling, Skin Wrap